The role of impulsive processes in self-determination theory: investigating the effects of implicit and explicit measures of motivation across a range of behaviours - Keatley, David (2013)
The current thesis reports six studies investigating the predictive validity and effects of implicit and explicit measures of motivation from self-determination theory (SDT; Deci & Ryan, 2008; Edmunds, Ntoumanis, & Duda, 2007; Ryan & Deci, 2000b), across a range of behaviours. In addition, the suitability of a dual-systems model (Strack & Deutsch, 2004) as a conceptual framework to understand the effects of implicit and explicit measures of motivation is also addressed. The research in this thesis, which focuses on integrating implicit processes and self-determination theory literature, was a novel area at the commencement of research. Therefore, the research conducted is of central importance in adding to the literature by examining the effects of implicit processes on motivation, thereby providing a better overall picture and adding knowledge by incorporating implicit processes alongside explicit measure from SDT.